2016
DOI: 10.1128/jvi.01258-16
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Herpes Simplex Virus 1 Tegument Proteins UL51 and UL14 and Its Role in Virion Morphogenesis

Abstract: To investigate the molecular mechanism(s) by which herpes simplex virus 1 (HSV-1) tegument protein UL51 promotes viral replication, we screened for viral proteins that interact with UL51 in infected cells. Affinity purification of tagged UL51 in HSV-1-infected Vero cells was coupled with immunoblotting of the purified UL51 complexes with various antibodies to HSV-1 virion proteins. Subsequent analyses revealed that UL51 interacted with another tegument protein, UL14, in infected cells. Mutational analyses of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
6
24
0
Order By: Relevance
“…In the nuclei of 7D-infected cells nucleocapsids were not affected, but in the cytoplasm of 7D-infected cells the number of defective viral particles, namely, envelope-defective particles, increased dramatically. This indicates that pORF7 is involved in secondary envelopment, probably by conjugating with other tegument proteins or glycoproteins to facilitate the formation of a tegument-glycoprotein complex to aid in anchoring the envelope layer to the capsid outer surface (35,36). Interestingly, the severity of envelopment deficiency caused by ORF7 deletion is different among the various cells used.…”
Section: Deletion Of Vzv-orf7 Affects Viral Envelopmentmentioning
confidence: 88%
“…In the nuclei of 7D-infected cells nucleocapsids were not affected, but in the cytoplasm of 7D-infected cells the number of defective viral particles, namely, envelope-defective particles, increased dramatically. This indicates that pORF7 is involved in secondary envelopment, probably by conjugating with other tegument proteins or glycoproteins to facilitate the formation of a tegument-glycoprotein complex to aid in anchoring the envelope layer to the capsid outer surface (35,36). Interestingly, the severity of envelopment deficiency caused by ORF7 deletion is different among the various cells used.…”
Section: Deletion Of Vzv-orf7 Affects Viral Envelopmentmentioning
confidence: 88%
“…This suggests that the pUL7-pUL51 complex may be important for recruitment of the other tegument proteins to secondary envelopment sites and/or the coordinated assembly of tegument-envelope and tegument-capsid interactions necessary for efficient HSV-1 assembly. Interestingly, a recent report demonstrated that pUL14, another conserved tegument protein, interacts with pUL51 in HSV-1-infected cells, and inhibition of this interaction also caused defects in secondary envelopment (27). Furthermore, these studies demonstrated that deletion of pUL14 had similar effects on HSV-1 replication and assembly as the deletion of pUL51, suggesting that these two proteins may also function as a complex during virus assembly.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 structural proteins are known to accumulate at juxtanuclear compartments, and virion assembly occurs at membranes that contain cellular trans -Golgi network and endosome marker proteins (5, 28). It therefore seems likely that pUL51 and pUL7 localized at these juxtanuclear compartments act in concert to aid virus assembly and secondary envelopment, perhaps in conjunction with pUL14 (27). …”
Section: Discussionmentioning
confidence: 99%
“…Roles in envelopment for the viral protein UL71 and its interacting protein UL103 have recently become well established (7)(8)(9)(10). Furthermore, the alphaherpesvirus homologues UL7 and UL51 also play roles in virus assembly and spread (11)(12)(13). Thus, UL71 may function by recruiting the ESCRT-III complex, which subsequently recruits VPS4.…”
mentioning
confidence: 99%